The impact of the Land Restitution Programme on the livelihood of rural communities : a case study of Ga-Makgato Community in Limpopo Province of South Africa - Mandiwana, Tshamano Donald (My University, 2014)
This study aimed to assess the impact of the Land Restitution Programme on the livelihoods of the rural communities of Ga-Makgato village in the Molemole Municipality, Limpopo Province. As a basis of assessment, the primary and secondary data were collected and analysed. Electronic and non-electronic sources were used to collect secondary data while primary data were collected through pre-tested questionnaires. The study found that both males and females who are 38 in number participate in the land restitution programme. Of this number, 8% was found to be the youth, while the elderly and adults population of the beneficiaries of the CPA constitute 92%. Females constitute 47%, while the percentage of their male counterparts stood at 53%. In terms of the level of literacy, 11% of the total number of beneficiaries could not read or write and this is a serious concern of this study. Analysis of number of jobs created was also carried out. It was found in this study that the CPA managed to create on 38 jobs. In as far as income generating ability of the CPA is concerned, R1,5million was generated during the period under review. Of this amount, R710 000-00 came from the sales of Nguni cattle while the Bonsmara generated R650 000- 00. The following challenges were established in this study, i.e., lack of sufficient grazing space, lack of access to adequate funding, lack of technical and financial management skills, lack of sufficient government support, lack of access to adequate water sources, lack of access to markets, high electricity bills and lack of proper record keeping systems. 4 The following recommendations are provided:  The CPA should review the lease agreement;  LEDA should in consultation with other financial institutions assist the CPA in accessing funding;  The Department of Agriculture should provide the CPA with technical assistance;  The Department of Water Affairs and Agriculture should ensure supply of water and infrastructure;  The Department of Agriculture and LEDA should provide the beneficiaries of the CPA with market infrastructure and information;  The Molemole Local Municipality should provide subsidy for electricity bills; and  Policy makers should consider implementation of the job creation model provided in this study. If these policies can be successfully implemented, the land restitution programme in the Capricorn District, particularly at Ga-Makgato and surrounding villages, can become a major strategy for improving the livelihoods of the rural poor.
Thesis (M. Dev.) --University of Limpopo, 2014
Keywords: Land restitution; Land reclamation; 333.310968; Land reform -- South Africa -- Limpopo; Reclamation of land -- South Africa -- Limpopo; Land settlement -- South Africa -- Limpopo; Land tenure -- South Africa -- Limpopo